Additions to the knowledge of the fauna of the tribe Cryptini Kirby, 1837 (Hymenoptera, Ichneumonidae, Cryptinae) of Iran - Heydari, Maryam Zardouei; Rakhshani, Ehsan; Mokhtari, Azizollah; Schwarz, Martin (Zootaxa, 2021)
Using Malaise traps, sweep nets and yellow pan traps during 2013–2015 in various localities of Iran, 18 species belonging to 11 genera in the tribe Cryptini Kirby, 1837 (Hymenoptera, Ichneumonidae, Cryptinae) were collected. Among them, five species including Aritranis longicauda (Kriechbaumer, 1873), Gambrus ornatus (Gravenhorst, 1829), Mesostenus dentifer (Thomson, 1896), Mesostenus kozlovi Kokujev, 1909 and Stenarella domator (Poda, 1761) are new records for the fauna of Iran. Sixty other species previously recorded from Iran are considered credible, bringing the number of known Iranian Cryptini to 65 species.